Pengaruh Kualitas Produk dan Promosi dalam Meningkatkan Volume Penjualan Mi Lidi (Studi di UD NNR Jaya Desa Sumuragung, Kecamatan Baureno, Kabupaten Bojonegoro) - Linda Widiawati; Akhmad Sirojuddin Munir; Dymas Yulia Putri Kusumaningtyas (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2019)
UD NNR Jaya is one of the snack food businesses that produces Mie sticks in Sumuragung Village, With many competitors engaged in the food sector, it is hoped that UD NNR Jaya can continue to increase the sales volume of its products to be able to maintain its trading business position in the midst of society in an era of business competition getting tighter. This is because each company will try to differentiate and provide added value to the products on offer. Among the factors that affect sales volume are product quality and promotion. The purpose of this study was to determine whether product quality had an effect on the sales volume of UD NNR Jaya stick noodles, and whether promotion had an effect on the sales volume of UD NNR Jaya stick noodles. The author uses quantitative research in this study. Samples were taken from 96 consumers of UD NNR Jaya. The method of data collection in this study is primary or directly from the questionnaire. Data analysis techniques in this study are validity test, reliability test, and hypothesis testing. The hypothesis test used in this study is the t test, and the (R2) test. The results of this study concluded that the value of tcount for variable X was 1.095 while ttable was 1.985, so tcount (1.095) < ttable (1.985), then the quality of the product partially had no effect on the sales volume of UD NNR Jaya stick noodles. And the value of tcount for variable X is -0.010, while ttable is 1.985, then tcount (-0.010) < ttable (1.985). So the promotion partially has no effect on the sales volume of UD NNR Jaya stick noodles.